Asia-Pacific film co-productions theory, industry and aesthetics - Jin, Dal yong 1964-; Su, Wendy (Routledge studies in media and cultural industries, 2021)
"This book examines cross-regional film collaboration within and beyond the Asia-Pacific region. Through a mixed methods approach of political economy and industry, market and textual analysis, the book contributes to the understanding of the global fusion of cultural products and the reconfiguration of geographic, political, economic, and cultural relations. Issues covered include: cultural globalization and Asian regionalization; identity, regionalism, and industry practices and inter-Asian and trans-Pacific co-production practices among the U.S., China, South Korea, Japan, India, Hong Kong, Argentina, Australia, Taiwan, and New Zealand"--